Dirty Voice: Revealing the Veil of Black Campaigns in the World of Politics in the 2024 Election - Tedjokusumo, Dave David; Siswanto, Carissa Amanda; Dewantara, Yuni Putri (IHSA Institute, 2024)
General elections (elections) are the main pillar of democracy, giving the people the right to choose their leaders and determine the direction of the nation, but this crucial process is often polluted by practices such as black campaigns. Smear campaigns aim to bring down political opponents by spreading false information, slander and negative propaganda. This practice not only tarnishes the good names of election participants, but also damages the integrity of democracy itself. This research uses a normative juridical approach. This research focuses on three problems, the first is the impact of black campaigns on the quality of democracy and election integrity in Indonesia, especially in the documentary film Dirty Vote, the second is the legal provisions that apply regarding black campaigns in Indonesia. election regulations, and the third is preventive strategies and policies that can be implemented to reduce black campaign practices in the next election. The research results show that black campaigns have a significant negative impact on the quality of democracy and election integrity in Indonesia. This practice is a serious challenge that must be faced. Comprehensive efforts involving regulatory improvements, law enforcement, and public education are critical to combating these dirty practices and achieving quality elections